الأخطاء الشائعة في مهارة الكلام لدى الطلبة الجدد بجامعة كياهي الحاج عبد الحليم موجوكرتو - Azimah, Nahdliyyatul; Hakim, Rahman; Su'ada, Fatkhiyatus (Universitas Negeri Semarang, 2021)
This study aims to describe the common mistakes that occur in new students majoring in Arabic on the practice of speaking skills. This type of research is qualitative through a descriptive approach. Collecting data through the method of speaking, listening, and observing. The results of this study indicate that the forms of language errors that often occur are in 1) phonology, 2) morphology, and 3) syntactic. In the phonological aspect, there are replacements in the pronunciation of hijaiyah letters, additions in pronunciation, and omissions. In the morphological aspect, errors were found in the use of auzānul fi'il, tastniyah, and jama' muannast salim. In the syntactic aspect, errors were found in the use of dhamāir munfasilah and muttashilah, jar majrūr, tarkīb na'ti, tarkīb 'adadi, jumlah fi'liyah, and jumlah ismiyah. To face these previous problems, the teacher provided the treatments on the following forms: (1) Presenting the pronunciation of Arabic letters and the pronunciation of the vocabulary intact. (2) Introduce short expressions. (3) Presenting sentence patterns. (4) Providing short dialogues, and certainly all of these qualities are applied to these students gradually and continuously in the class in the form of two-by-two. In addition, all these treatments were presented by the teacher through podcasts and YouTube, the crazy method, the rhetorical method, and the problem-solving method